(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Environmental Tax is deemed as one of the most important tools that can be used to eliminate the problem of oil –based environment pollution resulted out of oil products processes and this has been significantly approved by the experience in those leading countries in the field of protecting the environment against pollution whereas oil-producing countries which are rather awkward in maintaining the environment such as Iraq , suffer from notorious environmental effects pertaining to oil product processes. The problem of the research is represented the increased and constant rise in the volume of the environmental pollutants resulted from the processes managed by the international companies stationed in Basra and contracted with Iraqi government. Reports and researches which have been conducted by various Governmental bodies show the increase of pollutants ratios caused by oil industry in Basra Governorate continuously and increasingly that such ratios have acceded international and local standards. Thus, this present research seeks to demonstrate the importance of the environment tax as an active economical tool to avoid the environmental pollution caused by the activities of the international companies contracted to work in Iraq. The research has summed up to some conclusions, the most important of which is “Imposing an environmental tax over pollution caused by the activities of oil international companies shall lead to deter such type of pollution “. In the light of suchconclusions, some recommendations of this research are demonstrated herein, the most important of which is that “the necessity to impose the environmental tax over the activities of the international oil companies being contracted to work in Iraq since such tax is deemed as an active tool for the environmental policy by legislating a Code whose purpose is to protect environment against oil pollution “.